2020
DOI: 10.1021/acsabm.0c00920
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Natural Composition of Brown Seaweed for the Preparation of Hybrid Ink for 3D Printing of Hydrogels

Abstract: This study aims to utilize the natural composition of brown seaweed by deriving alginate and cellulose concurrently from the stipe (stem-like) and blade (leaf-like) structures of the seaweed; further, this is followed by fibrillation for the direct and resource-efficient preparation of alginate/cellulose nanofiber (CNF) hybrid inks for three-dimensional (3D) printing of hydrogels. The efficiency of the fibrillation process was evaluated, and the obtained gels were further studied with regard to their rheologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Moreover, the resulting cellulose, chitin and chitosan scaffolds exhibited high strengths of 0.68, 0.84, and 0.46 MPa (Figure l,m) at an 80% strain and Young’s modulus of 93.8, 120.9, and 48 kPa (Figure m), respectively, indicating the high structure integration and strong interaction among the filaments. Noticeably, most of the 3D-printed natural polymeric hydrogel strengths were usually less than 0.2 MPa. , Cyclic compression tests revealed that the scaffolds were elastic, which allowed the constructs to resist multiple compression deformations and retain their original hierarchical structures during applications (Figure n,o,p,q). Furthermore, the FS nanoparticles as a sacrificial carrier material could be almost completely removed by immersing the scaffolds in 5 wt % NaOH solution for 4 h without defecting the nanofibrous structure (Figure S19) for diverse applications.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the resulting cellulose, chitin and chitosan scaffolds exhibited high strengths of 0.68, 0.84, and 0.46 MPa (Figure l,m) at an 80% strain and Young’s modulus of 93.8, 120.9, and 48 kPa (Figure m), respectively, indicating the high structure integration and strong interaction among the filaments. Noticeably, most of the 3D-printed natural polymeric hydrogel strengths were usually less than 0.2 MPa. , Cyclic compression tests revealed that the scaffolds were elastic, which allowed the constructs to resist multiple compression deformations and retain their original hierarchical structures during applications (Figure n,o,p,q). Furthermore, the FS nanoparticles as a sacrificial carrier material could be almost completely removed by immersing the scaffolds in 5 wt % NaOH solution for 4 h without defecting the nanofibrous structure (Figure S19) for diverse applications.…”
Section: Resultsmentioning
confidence: 99%
“…After purification, the fibrillation process resulted in the separation of the cellulosic part into very fine nanofibers through the shearing forces applied to the sample by ultrafine grinding, resulting in a gel composed of alginate and CNFs ( Figure 1 c). The characterization of the gel structure was reported in our previous study, 23 and the gel composition is summarized in the Materials section. The ACNF gel was then ice-templated and freeze-dried to form an anisotropic ACNF aerogel structure ( Figure 1 d) and treated with solutions of CaCl 2 in ethanol to generate a crosslinked sample (ACNF-X) ( Figure 1 e,f).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the measured energy consumption for their mechanical separation process is remarkably low (1.0 kW h kg –1 ); meanwhile, the commercially bleached wood kraft pulp consume 8.4 kW h kg –1 for a similar mechanical processing. 23 In a previous study, we have systematically evaluated the approach of direct bleaching, followed by mechanical separation of industrial residue. 54 This resulted in a reduced environmental impact of more than 75% for carbon footprint, along with a cost reduction of more than 50%, owing to an increased yield and reduced energy, chemical, and water use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations